Who Borrows from the Lender of Last Resort? - DRECHSLER, ITAMAR; DRECHSEL, THOMAS; MARQUES‐IBANEZ, DAVID; SCHNABL, PHILIPP (Journal of Finance, 2016)
ABSTRACT We analyze lender of last resort (LOLR) lending during the European sovereign debt crisis. Using a novel data set on all central bank lending and collateral, we show that weakly capitalized banks took out more LOLR loans and used riskier collateral than strongly capitalized banks. We also find that weakly capitalized banks used LOLR loans to buy risky assets such as distressed sovereign debt. This resulted in a reallocation of risky assets from strongly to weakly capitalized banks. Our findings cannot be explained by classical LOLR theory. Rather, they point to risk taking by banks, both independently and with the encouragement of governments, and highlight the benefit of unifying LOLR lending and bank supervision.